An empirical assessment of the contribution of financialization and corporate governance to the rise in income inequality - Petra Dünhaupt (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
This paper investigates the impact of financialization and changes in corporate governance on income inequality for a sample of 13 OECD countries between 1980 and 2010. Though financialization and changes in corporate governance have been widespread, there has been little empirical analysis of the link between these phenomena and the rise in income inequality. Since the 1980s, many countries liberalized their financial markets, deregulated their labor markets, and corporate governance has increasingly focused on shareholder value. Three decades later, income inequality has grown considerably. Above all, there is an increased stratification at the very top of the income distribution. Regarding this situation, it is argued that financialization and hence changes in corporate governance are relevant contributors to the rise in income inequality. Our results suggest that a rise in shareholder value orientation measured by stock market capitalization and dividend payments of non-financial corporations, the unemployment rate, technological change and the old age dependency ratio, contribute to the increase in inequality, while union density, trade openness, economic growth and social spending are associated with a decline in inequality. In regard to the top income share, our results suggest that stock market capitalization and dividend payments contributed to the rise in top shares, whereas union density, trade openness, economic growth and top marginal tax rates compress top shares.
Keywords: D31; F61; F65; F66; G3; 330; Gini-coefficient; inequality; top income share; financialization; shareholder value